2021
DOI: 10.1016/j.ynstr.2021.100310
|View full text |Cite
|
Sign up to set email alerts
|

The impact of child abuse on the neurobiology of self-processing in depressed adolescents

Abstract: Child abuse is linked to lifetime psychopathology including abnormal self-processing. Given self-processing maturation in adolescence, we tested duration, presence, and abuse accumulation's impact upon self-processing neurobiology among depressed youth with (N = 54) and without an abuse history (N = 40). Youth evaluated positive and negative self-descriptors across four points of view in the scanner. Regression analyses showed that longer abuse duration (in days) was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Interestingly, our chain mediation analyses suggested that childhood trauma experiences may first be linked to physical self-concept and then to social self-concept, ultimately resulting in depression. Previous research has shown that childhood trauma may increase negative self-processing by reducing brain activity in regions associated with socioemotional processes [ 61 ]. This reduction in brain activity may contribute to lower self-image, acceptance, and self-esteem, resulting in anxiety and depressive symptoms [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our chain mediation analyses suggested that childhood trauma experiences may first be linked to physical self-concept and then to social self-concept, ultimately resulting in depression. Previous research has shown that childhood trauma may increase negative self-processing by reducing brain activity in regions associated with socioemotional processes [ 61 ]. This reduction in brain activity may contribute to lower self-image, acceptance, and self-esteem, resulting in anxiety and depressive symptoms [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depression was known to be one of the common consequences of child abuse that extended to adulthood [ 78 ]. In this study, there was a negative correlation between depression and asymmetry or horizontal arm position (signifying crying for help, poor self-esteem, and avoiding contact with environment).…”
Section: Discussionmentioning
confidence: 99%